2016
DOI: 10.1051/matecconf/20167801104
|View full text |Cite
|
Sign up to set email alerts
|

Study on Modified Sand Filtration Towards Water Quality of Wet Market Waste Water

Abstract: Abstract. Investigation on the potential of sand filter as a pre-treatment of waste water was done in Kangar wet market, Perlis. Besides, the best composition of filter in order to treat wastewater based on BOD, COD, SS, AN, turbidity and pH levels are further examined. In this study, there are four types of sand filter composition which the medias consist of fine sand and coarse sand while the modified sand filter are consist of sand, course sand and activated carbon prepared from rice husk and coconut shells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 6 publications
2
1
0
Order By: Relevance
“…Turbidity reduces because of the reduction of suspended and dissolved solids. Few research studies reported that the sand filtration using activated carbon is a superior method and reduces mainly pH, TDS, turbidity and COD when the wastewater is passed through it (Prasad et al 2006;Khalaphallah 2012;Saad et al 2016). The same has been observed in the present study using the above technique.…”
Section: Treated Greywatersupporting
confidence: 84%
“…Turbidity reduces because of the reduction of suspended and dissolved solids. Few research studies reported that the sand filtration using activated carbon is a superior method and reduces mainly pH, TDS, turbidity and COD when the wastewater is passed through it (Prasad et al 2006;Khalaphallah 2012;Saad et al 2016). The same has been observed in the present study using the above technique.…”
Section: Treated Greywatersupporting
confidence: 84%
“…Turbidity values for the RCHP were relatively lower than CCHP due to the adsorbent's low porosity and surface area. Turbidity removal by the Control is consistent with the available literature on turbidity removal by sand filters (Saad et al, 2016) in that sand and gravel grains are known to remove suspended matter in greywater, thereby making wastewater less turbid (Samayamanthula et al, 2019). From an influent of 58 TCU, results obtained for color in the treated effluent were 10 TCU, 69 TCU, and 63 TCU for CCHP, RCHP, and Control.…”
Section: Turbidity and Coloursupporting
confidence: 84%
“…These results indicate that the entire treatment process is capable of removing bacteria, especially faecal coliforms which are the mostly causative of waterborne infection (Suvadhan, 2014). It has long been known that sand has been used as a filter to purify drinking water in many industry (Saad et al, 2016), and silica sand has been used to purify water as it has ability to trap microorganism (Rafael, 1992).…”
Section: Assessment Of Ag Nps-silica Sand Filter Performance For Bact...mentioning
confidence: 94%